Paraneoplastic Syndromes Associated with Laryngeal Cancer - Rinaldo, Alessandra (Adv Ther, 2019)
OBJECTIVES: Paraneoplastic syndromes occur rarely in association with laryngeal cancer. When present, the syndrome may be the first sign of the malignancy. The aim of the present study was to review and report on all published cases in the international literature. METHODS: A search of PubMed was conducted for “paraneoplastic syndromes in laryngeal cancer” without any restrictions on language or publication year. The full texts of all relevant articles were reviewed and all cases of paraneoplastic syndromes associated with any type of laryngeal cancer were extracted and analyzed. RESULTS: We identified 59 cases of paraneoplastic syndromes related to laryngeal cancer in the literature published from 1963 until recently. There were 46 squamous cell carcinomas and 10 neuroendocrine carcinomas. Twenty-two of the paraneoplastic syndromes involved the endocrine system, 21 were dermatologic or cutaneous, 8 neurologic, 5 osteoarticular or rheumatologic, 1 ocular, 1 muscular, and 1 hematologic. Treatment strategies included surgery, radiotherapy, chemotherapy, and often multimodal therapy, depending on the histology and stage of the laryngeal cancer. CONCLUSIONS: Because of their rarity, paraneoplastic syndromes associated with laryngeal cancer are difficult to diagnose. By presenting and systematically reviewing all published cases in the international literature, the present review may help clinicians to recognize them and to suspect the diagnosis of laryngeal cancer at an earlier stage than otherwise might be possible.